2016
DOI: 10.31248/jasvm2016.029
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastrointestinal helminths of Tilapia zilli (Gervias) in Gombe, Northeastern Nigeria

Abstract: In order to determine the prevalence of gastrointestinal helminths infestation in tilapia species sold in major markets in Gombe, three hundred (300) tilapia fish samples of both sexes and of different age groups were randomly examined. The sample population included 183 adults and 117 juveniles fishes, 157 females and 143 male fishes. Out of the total fishes sampled from three local fish markets, 128 (42.70%) were found to be infested by gastrointestinal helminthes. The prevalence of gastrointestinal helminth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
3
2
2
Order By: Relevance
“…This study also harvested the parasites from the abdominal cavity, stomach, and intestine of host fish. This is similar to the findings of various studies showing the gastrointestinal tract to be the preferred site among parasitic helminths (Gosselle et al, 2008;Onyedineke et al, 2010;Dauda et al, 2016). It is important to note that the method implemented for isolation and examination of the parasites was the common routine visual observation coupled with identification based on taxonomic descriptions from previous studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study also harvested the parasites from the abdominal cavity, stomach, and intestine of host fish. This is similar to the findings of various studies showing the gastrointestinal tract to be the preferred site among parasitic helminths (Gosselle et al, 2008;Onyedineke et al, 2010;Dauda et al, 2016). It is important to note that the method implemented for isolation and examination of the parasites was the common routine visual observation coupled with identification based on taxonomic descriptions from previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…The final sequence alignment for each marker was converted to a PAUP/NEXUS file in Data Analysis in Molecular Biology and Evolution (DAMBE) (Xia, 2013). The optimal model of evolution was chosen according to the Akaike Information Criterion (AIC) using jModelTest 1 (Darriba et al, 2012). In the 18S final sequence dataset, the TrNeF + G model (Tamura and Nei, 1993) was implemented involving 34 nucleotide sequences, with a total of 628 positions.…”
Section: Purification and Dna Sequence Analysismentioning
confidence: 99%
“…The obtained prevalence was relatively higher than the 18.7% reported by Biu & Nkechi (2013) in the same study area. It is, however, lower than the 42.7% reported by Dauda et al (2016). The differences in the prevalence of helminths in the present study and the results of previous studies may be due to differences in the aquatic origin of fishes and changes in the epidemiology of parasitic infections due to the influence of environmental variables and time passage.…”
Section: Discussioncontrasting
confidence: 87%
“…The result agrees with Uhuo et al (2014), who reported Acanthocephalans as the dominant helminths in tilapia. However, unlike this finding, Dauda et al (2016) reported nematodes as the dominant helminth. The prevalence and intensity of helminthiasis in tilapia depend on parasite species and their biology, the feeding habits of the host, physical factors, hygiene of the aquatic environment, and the presence of intermediate host species (Olurin et al, 2012;Nimbalkar & Deolalikar, 2015).…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation